Mixed-Thickness Tunnel Access (MiTT) through a linear vertical mucosal incision for a minimally invasive approach for root coverage procedures in anterior and posterior sites: technical description and case series with 1-year follow-up - Marques, Tiago (2023)
Purpose: The goal of this article was to introduce a new root coverage (RC) technique, the mixed-thickness tunnel access (MiTT) technique, which approaches a full-split design and intends to augment soft tissues coronal to the gingival margin. It was shown step-by-step, and the results were presented in a case series. Methods: Healthy individuals (non-diabetics) and non-smokers with gingival recession (GR) type 1 or 2 (RT1 or RT2) were included. After evaluation, prophylaxis was performed 14 days before the surgical procedure. During the surgical appointment, one or two vertical incision(s) on the mucosa (around 1–2 mm apical to the MGJ), lateral to the papilla base, was/were performed after anesthesia. Initially, there was a partial incision to detach the mucosa of the muscles (split design). It was permitted (but not mandatory) to perform intrasulcular incisions. Through the vertical incision, internally, subperiosteal access from the MGJ toward the gingival margin (coronally) was performed to create a full-thickness tunnel. Then, communication from the vertical incision with the gingival sulcus and the papilla base occurred, keeping the papilla tip intact. A connective tissue graft was harvested and inserted through the linear incision or intrasulcularly. There were interrupted sutures. An adjunctive material may be applied (e.g., Endogain). The root coverage was measured using a periodontal probe and considered fully covered when the gingival margin was 1 mm coronal to the cementum–enamel junction (CEJ). Results: Nine healthy individuals (seven females and two males) aged 19 and 43 were enrolled. They were treated following the MiTT steps. Four cases had a single GR; two patients had two teeth involved; and three others had three or four GR. There were seven cases of RT1 and two RT2. All RT1 cases achieved 100% RC, while the mean RC obtained for RT2 was around 80%. Conclusion: The MiTT technique can be considered a more straightforward approach for minimally invasive surgical techniques, which is a feasible option to treat RC with a high success rate, predictability, and esthetic preservation. Therefore, there is a technical sensitivity to performing the full-split design procedure.